Nutritive Value and In-Vitro Digestibility of Blended Ratios of Wheat Offal and Wet Sorghum Brewer Residue as Feed for Livestock - Ayandiran, Samuel Kola; Adedokun, Mathew Adewale; Adekunle, Ibironke (Journal of Applied Animal Science, 2025)
The use of agro-industrial by-products as animal feeds has been a matter of interest for the last few decades. Hence, this study evaluated the chemical composition, volatile fatty acid profile, and in-vitro digestibility of blended ratios of wheat offal and wet sorghum brewer residue. Fresh wet sorghum brewer residue (WSBR) was collected from local gin (Burukutu) producers and blended with wheat offal (WO) on a weight-for-weight basis in the following rations: 1WO:1WSBR, 1WO:1.5WSBR, 1WO:1.2WSBR, 1WO:2.5WSB, 1WO:1.3WSBR, and 1WO:3.5WSBR, arranged in a Completely Randomized Design. The blends were air-dried for 3 days at 39 °C. Samples of blended ratios were analyzed for chemical composition, volatile fatty acids profile, and in-vitro digestibility using standard procedures. The dry matter contents of ratios 1:1, 1:2, 1:2.5, 1:3, and 1:3.5 were significantly higher (p < 0.05) than the 1:1.5 ratio. The crude fibre content significantly increased (p < 0.05) as the proportion of WSBR increased in the blends. The carbohydrate fractions of ratios 1:2, 1:2.5, and 1:3 were significantly higher (p < 0.05) than those of ratios 1:1 and 1:1.5. The neutral detergent fibre was significantly higher (p < 0.05) in ratio 1:3.5 than in other blended ratios. Furthermore, the hemicellulose content was significantly higher (p < 0.05) in ratios 1:1.5, 1:2.5, and 1:3 than in ratio 1:1, and was lowest in 1:3.5. However, ratios 1:1 and 1:1.5 had significantly higher (p < 0.05) acetic, propionic, butyric, valeric, and lactic acid contents than the other ratios. Notably gas production was significantly highest (p < 0.05) in ratio 1:1 from 3 to 24 hours of in-vitro digestibility compared to other ratios. It could be concluded that blended ratios of wheat offal and wet sorghum brewer residue improved nutrient availability for livestock animals; however, ratios 1:1 and 1:1.5 produced more in-vitro gases, while ratios 1:1, 1:1.5, and 1:2 showed superior dry matter digestibility.